CO2 Uptake Performance of Climbing Plant Wall - Sunakorn, Pasinee; Kasemsap, Poonpipope (Journal of Architectural/Planning Research and Studies (JARS), 2018)
Carbon dioxide is the major greenhouse gas that increase rapidly during th past two centuries. Growing trees to absorb Carbon dioxide is a fundamental effort to mitigate global warming, but was always limited in high density city. Climbing plants on wall can also be a solution to increase green area and absorb Carbon dioxide as much as growing trees or shrubs on ground, if receive enough sunlight, by occupying much less ground area. This research aims to study CO2 uptake performance of different climbing plants which are local for Thailand, low maintenance, good leaf coverage and fast growing. Two experiments were carried out. The first one is to find CO2 uptake from Photosynthesis rate measured on leaves with different ages, comparing three climbing plants. The second experiment was carried out on 1x1 m panel covered with climbing plants on both side, to find real amount of CO2 uptake from air chamber. It was founded that three selected climbing plants perform differently. Thunbergia grandiflora has the highest rate of CO2 uptake, while Antigonon leptopus and Coccinia grandis rank in second and third in both experiments. The maximum amount of CO2 uptake of 1x1 m Thunbergia grandiflora wall is 20 ppm, Antigonon leptopus 15 ppm, Coccinia grandis 5 ppm from 1 M3 air per 10 seconds.